Lattice plainification advances highly effective SnSe crystalline thermoelectrics - Liu, Dongrui; Wang, Dongyang; Hong, Tao; Wang, Ziyuan; Wang, Yuping; Qin, Yongxin; Su, Lizhong; Yang, Tianyu; Gao, Xiang; Ge, Zhenhua; Qin, Bingchao; Zhao, Li-Dong (Science (American Association for the Advancement of Science), 2023)
Thermoelectric technology has been widely used for key areas, including waste-heat recovery and solid-state cooling. We discovered tin selenide (SnSe) crystals with potential power generation and Peltier cooling performance. The extensive off-stoichiometric defects have a larger impact on the transport properties of SnSe, which motivated us to develop a lattice plainification strategy for defects engineering. We demonstrated that Cu can fill Sn vacancies to weaken defects scattering and boost carrier mobility, facilitating a power factor exceeding ~100 microwatts per centimeter per square kelvin and a dimensionless figure of merit ( ZT ) of ~1.5 at 300 kelvin, with an average ZT of ~2.2 at 300 to 773 kelvin. We further realized a single-leg efficiency of ~12.2% under a temperature difference (Δ T ) of ~300 kelvin and a seven-pair Peltier cooling Δ T max of ~61.2 kelvin at ambient temperature. Our observations are important for practical applications of SnSe crystals in power generation as well as electronic cooling. Thermoelectric materials interconvert heat and electricity, making them useful for a range of devices. Liu et al . added copper to tin selenide, which improved the thermoelectric and mechanical properties near room temperature (see the Perspective by Chung). Tin selenide tends to have several defects when synthesized, including tin vacancies. The copper occupies these intrinsic tin vacancies, leading to improved carrier mobility. The overall strategy creates a lattice less riddled with vacancies, which could be useful for other materials. —Brent Grocholski Introducing copper to a sodium-doped tin selenide improves the room temperature thermoelectric properties.